Dexamethasone for unresponsive diabetic macular oedema: optical coherence tomography biomarkers. Issue 4 (14th October 2018) - Bonfiglio, Vincenza; Reibaldi, Michele; Pizzo, Alessandra; Russo, Andrea; Macchi, Iacopo; Faro, Giuseppe; Avitabile, Teresio; Longo, Antonio
Abstract: Purpose: To analyse the effects of intravitreal dexamethasone implant (DEX) in patients with diabetic macular oedema (DME) unresponsive to ranibizumab treatment, in relation to the inflammatory optical coherence tomography (OCT) retinal features, subfoveal neuroretinal detachment (SND) and hyperreflective retinal spots (HRS). Methods: Patients with DME poorly responsive to three injections of ranibizumab were treated with DEX. Best‐corrected visual acuity (BCVA) and central macula thickness (CMT, measured by Spectralis SD‐OCT) were assessed at baseline and at 1, 3, and 6 months. Results: Overall, 44 eyes were included in the study. In the whole group, mean BCVA (baseline 51.5 ± 8.3 letters) increased significantly at 1 month (to 56.9 ± 8.8 letters; Tukey HSD p = 0.017) and was 55.5 ± 8.8 letters at 3 months (Tukey HSD p = 0.128). Central macula thickness (CMT) reduced significantly at 1 and 3 months (417 ± 149  μ m and 469 ± 128  μ m, respectively, both Tukey HSD p < 0.001 versus baseline). Subgroup analysis showed a significant BCVA increase at 1 month in eyes with SND + HRS (from 51.2 ± 9.2 to 58.2 ± 9.0, p = 0.029), and a trend to BCVA increase in eyes with HRS (from 52.3 ± 6.4 to 56.8 ± 7.9, p = 0.080), with a significant CMT decrease in both groups (p < 0.001). No changes of either parameter were found in eyes without SND and HRS. Conclusion: Spectral domain OCT is useful in identifying some inflammatory features in DME. Among DME eyes 'poorly responsive' to ranibizumab, those with SND and HRS responded better to DEX implants than those without these features.